Identification of alarm patterns using computational intelligence approach - Gupta Anubha (2014)
In today’s fast paced world, maintaining a high degree of equipment uptime and reliability is important. Development of effective approaches to monitor the health state of machines has always been a concern of industrial applications. Due to this, it is a requirement that an algorithm is developed which can pre-predict the failure events by identification of the alarm patterns in an industry database and proper preventive measures can be taken at the right time. The main objective of this project is to generate predictive patterns by importing industry data, processing it and then implementing it using SQL and Oracle Server. The results (patterns) generated are analyzed based on the user requirements.